Effectiveness Test of Sidaguri Leaf Ethanol Extract Gel (Sida rhombifolia L.) on the Cealing of Degree IIA Burn in Male Rabbits - Adani, Bazlina; Dalimunthe, Gabena Indrayani; Lubis, Minda Sari; Mambang, D Elysa Putri (Indonesian Journal of Science and Pharmacy, 2023)
Burns are one of the incidents that often occur in society. Currently, the use of burn medicine is very limited, in terms of the cost of treatment and healing is relatively expensive. In this case, the use of natural plants is needed as a treatment for burns on the skin, namely sidaguri leaves. Researchers want to take advantage of secondary metabolites contained in sidaguri leaves and formulate them into pharmaceutical preparations in the form of a gel. The purpose of this study was to determine the content of secondary metabolites in the ethanolic extract of sidaguri leaf and to determine the effectiveness of the gel preparation of the ethanolic extract of sidaguri leaf (Sida rhombifolia L.) on the healing of burns. This research includes simplicia characterization, phytochemical screening, gel evaluation and test the effectiveness of sidaguri leaf extract gel. HPMC negative control group, 1% EEDS, 3% EEDS, 5% EEDS and bioplacenton positive control group. The parameters tested were the diameter of the burn for 14 days. The research data were analyzed using the One-Way ANOVA (Analysis of Variance) method followed by the Tukey test. The results of this study obtained EEDS 5% and bioplacenton did not have a significant difference in the healing of burns in male rabbits on day 14.  It can be concluded that the ethanolic extract gel of sidaguri leaves has effectiveness on healing burns with a dose of 5% EEDS concentration.